2000
DOI: 10.1073/pnas.97.8.3890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of saturation mutagenesis of the phage SP6 promoter on transcription activity, presented by activity logos

Abstract: A full set of SP6 promoter variants with all possible single substitutions at positions ؊17 to ؉5 was constructed. Transcription activities of these variants were individually measured in vivo and in vitro to determine the contribution of each base pair to the promoter activity. The in vivo activity was measured indirectly by transcriptional interference of the replication of promoter-bearing plasmids. This activity depends most highly on residues ؊11, ؊9, ؊8, ؊7, and ؉1 (initiation site). All substitutions at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 25 publications
6
27
0
Order By: Relevance
“…The SP6 genome was searched for sequences that correspond to the SP6RP core promoter sequence (5Ј-ATTTAGGTGACACTATAG [53]). Thirteen related sequences were identified that have three or fewer mismatches; a degenerate consensus sequence, KAWTTARG KGACACTATAG, was derived based on the promoter sequences with two or fewer mismatches; and the search was repeated.…”
Section: Characterization Of Bacteriophage Sp6 Virionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SP6 genome was searched for sequences that correspond to the SP6RP core promoter sequence (5Ј-ATTTAGGTGACACTATAG [53]). Thirteen related sequences were identified that have three or fewer mismatches; a degenerate consensus sequence, KAWTTARG KGACACTATAG, was derived based on the promoter sequences with two or fewer mismatches; and the search was repeated.…”
Section: Characterization Of Bacteriophage Sp6 Virionsmentioning
confidence: 99%
“…No additional putative promoters were identified. Of the 13 sequences, 3 (ϩ1 positions at bp 2121, 6304, and 29410) are unlikely to function since they depart from the core sequence at positions 1, Ϫ1, and Ϫ15, respectively, which would dramatically decrease promoter activity (53). The remaining 10 sites are excellent candidates for SP6 promoters; based on saturation mutagenesis experiments, the departures of these sequences from the core consensus sequence should have little effect on promoter activity (Fig.…”
Section: Characterization Of Bacteriophage Sp6 Virionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This exlusivity of promoter specificity seems to be the trend among the T7-like phages (24,42,45), and it seems that there must be some selective pressure that resulted in this feature.…”
mentioning
confidence: 99%
“…1). Our previous study of saturation mutagenesis on the SP6 promoter suggested that the residue at −10 hardly contributes to transcription activity in vivo or in vitro (Shin et al, 2000), although it is mostly T among the 11 known SP6 promoters. Also, the SP6 residues at −12 are highly diverse and contribute little to promoter activity.…”
Section: Discussionmentioning
confidence: 98%